THE INFLUENCE OF CAPITAL ADEQUACY AND GOVERNANCE ON FINANCIAL PERFORMANCE WITH LIQUIDITY AS A MEDIATOR IN BPR IN EAST JAVA - Fetri Andriani; Surya Raharja (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This research aims to determine the relationship between capital adequacy and the implementation of governance on BPR performance with liquidity as a mediating variable. In scientific research, quantitative research is applied, with the resulting numerical data being analyzed statistically. The data used are regional data, namely the Capital Adelqulacy Ratio (CAR), the results of assessments of governance implementation, Loan to Delposit Ratio (LDR) and Ratio on Assets (ROA) of BPRs in East Java in the time period from January 2017 to December 2023. This research is carried out Inferential statistical analysis method. The ultimate data analysis process uses techniquesSEM (Structural Equation Modelling) PLS (Partial Last Squularel) and carried out through 2 (dula) models, namely the pengukuran model (outer model) and the struktural model (inner model). The research results show that capital abundance has a significant effect on BPR financial performance and BPR liquidity. The implementation of governance has had a significant positive impact on the company's financial performance but has not had a significant impact on BPR liquidity. The results of the research show that liquidity does not play a significant role as a mediator between governance and financial performance in the BPR context.Keywords: Good Corporate Governance, Liquidity, Capital Adequacy, Implementation of Governance, Financial Performance